2021
DOI: 10.11604/pamj.2021.40.170.24413
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking prevalence and associated factors among college students, Amhara, Ethiopia

Abstract: Introduction tobacco is the only legal drug that kills many of its users when used exactly as intended by the manufacturers. It is estimated that of the 1.1 billion smokers worldwide, nearly 80% of them live in low and middle-income countries. This trend increases in college and university students with most smokers starting to smoke during adolescent. The aim of this study is to assess cigarette smoking prevalence and associated factors among a select group of college of teachers´ education stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Cigarette smoking is one of the leading causes of preventable morbidity and mortality globally ( 1 ). The report of 2018 China-Global Adult Tobacco Survey (GATS) showed that the average age to initiating daily smoking for daily smokers was 21.1 years old ( 2 ), around the average age of a university student.…”
mentioning
confidence: 99%
“…Cigarette smoking is one of the leading causes of preventable morbidity and mortality globally ( 1 ). The report of 2018 China-Global Adult Tobacco Survey (GATS) showed that the average age to initiating daily smoking for daily smokers was 21.1 years old ( 2 ), around the average age of a university student.…”
mentioning
confidence: 99%
“…Another relatively low proportion of smoking was reported by Animut Takele Telayneh, et. al., , 2021 in their a study conducted amongst the Amhara, Ethiopia Teachers´ Education students, the prevalence of cigarette smoking is found to be also low ( Finally, the study and the other comparative ones mentioned in the discussion shared almost common independent factors associated with the phenomenon of cigarette smoking, notably having smoking friends and/or smoking colleagues, leisure, and means of relieving psychological pressure.…”
Section: Discussionmentioning
confidence: 88%
“…While the prevalence of smokers was 12.3% among students at Hawler Medical University/Iraq in 2007 [31], at Karbala University/Iraq in 2005 was 10.5% [32] while in 2009 it was 19.4% [33], 233 out of 500 students were smokers at Hilla college/ Babylon/Iraq in 2021 [34]. While among college students in other countries: Alkhalaf et alat KSA found 12.4% of medical students were smokers [35], 8.9% by Kabbash et al in Egypt [36], 15.1% in UAE by Ahmed et al [37], 51.4% by Alolabi et al [38] in Syria, 6.8% by Telayneh et al in Ethiopia [39]. The PCV level between smokers and non-smokers was also investigated and showed that the smokers had higher levels of PCV than non-smokers as shown by other researchers [40][41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%